Maquiavel e a função política da arte da guerra - Zorzo, Douglas Antônio Fedel (2015)
The political theory of Niccolò Machiavelli is permeated by a constant and inflexible preoccupation: the military question. The problems about the government relations are followed alongside by considerations about the political necessity of formation and organization of national armies. The Machiavellian military theory, diluted in the set of his works, is revealed as an essential aspect for the maintenance of state ordinations and the conservation of the vivere civile. The success of political institutions is dependent on the capacity for coordination and full absorption of the structures directed for the exercise of war: the military art and the political art create, at the heart of Machiavelli's thought, bonds of an inseparable articulation. The proper relation with the martial apparatus is a condition for the survival of States. In this sense, the primary objective of the study here presented is to delineate and to expose how the Machiavelli's warfare conceptions are thoughtful and grounded in the core of political arguments. On the one hand, we will seek to illustrate the function exercised by the art of war in the interior of the dynamic of state, evaluating the necessary requirements for the fusion of war and politics, beyond to devote one particular attention to the implications of this role in republicans and princely governments. On the other hand, we will intend to expose the way in which the interpretations of the technical nature of the military arrangements advocated by the Florentine secretary were strongly guided by government issues.